Endocrine disruptors and other inhibitors of 11β-hydroxysteroid dehydrogenase 1 and 2: Tissue-specific consequences of enzyme inhibition - Vitku, Jana; Starka, Luboslav; Bicikova, Marie; Hill, Martin; Heracek, Jiri; Sosvorova, Lucie; Hampl, Richard (The Journal of steroid biochemistry and molecular biology, 2016)
Numerous chemicals in the environment have the ability to interact with the endocrine system. These compounds are called endocrine disruptors (EDs). Exposure to EDs represents one of the hypotheses for decreasing fertility, the increased risk of numerous cancers and obesity, metabolic syndrome and type 2 diabetes. There are various mechanisms of ED action, one of which is their interference in the action of 11β-hydroxysteroid dehydrogenase (11βHSD) that maintains a balance between active and inactive glucocorticoids on the intracellular level. This enzyme has two isoforms and is expressed in various tissues. Inhibition of 11βHSD in various tissues can have different consequences. In the case of EDs, the results of exposure are mainly adverse; on the other hand pharmaceutically developed inhibitors of 11βHSD type 1 are evaluated as an option for treating metabolic syndrome, as well as related diseases and depressive disorders. This review focuses on the effects of 11βHSD inhibitors in the testis, colon, adipose tissue, kidney, brain and placenta.
Keywords: glukokortikoidy; mozek; placenta; Adipose Tissue; Endocrine Disruptors; Enzyme Inhibitors; mužské pohlaví; inhibitory enzymů; endokrinní disruptory; Male; Female; Humans; Inhibitor; 11-beta-Hydroxysteroid Dehydrogenase Type 1; Colon; 11-beta-hydroxysteroiddehydrogenasa typ 2; Diabetes Mellitus; Brain; lidé; Endocrine disruptor; ženské pohlaví; těhotenství; nádory; 11-beta-Hydroxysteroid Dehydrogenase Type 2; 11β-hydroxysteroid dehydrogenase; obezita; Obesity; diabetes mellitus; Placenta; Glucocorticoids; Organ Specificity; tuková tkáň; Metabolic Syndrome; testis; kolon; 11-beta-hydroxysteroiddehydrogenasa typ 1; Testis; Neoplasms; Pregnancy; metabolický syndrom; orgánová specificita; Adipose tissue